2014
DOI: 10.1109/tuffc.2014.006466
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic characterization of contrast-to-tissue ratio and axial resolution for dual-frequency contrast-specific acoustic angiography imaging

Abstract: Recently, dual-frequency transducers have enabled high-spatial-resolution and high-contrast imaging of vasculature with minimal tissue artifacts by transmitting at a low frequency and receiving broadband superharmonic echoes scattered by microbubble contrast agents. In this work, we examine the imaging parameters for optimizing contrast-to-tissue ratio (CTR) for dual-frequency imaging and the relationship with spatial resolution. Confocal piston transducers are used in a water bath setup to measure the SNR, CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 87 publications
4
54
0
Order By: Relevance
“…The low transmitting frequency element was designed at 2 MHz considering the resonant frequency of microbubbles and prior testing [6]. Thus, proper thickness, aperture, and material were then determined.…”
Section: A Design Methods and Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The low transmitting frequency element was designed at 2 MHz considering the resonant frequency of microbubbles and prior testing [6]. Thus, proper thickness, aperture, and material were then determined.…”
Section: A Design Methods and Materials Propertiesmentioning
confidence: 99%
“…In this technique, microbubbles are usually excited by low frequency acoustic waves (1-4 MHz) with moderate peak negative pressure and short pulse length near the resonant frequency of microbubbles; the high frequency (> 15 MHz) nonlinear echoes from microbubbles are received by a high frequency receiver [3,4]. Proper frequency combinations that produces high contrast-to-tissue ratio in super harmonic imaging, and high resolution have been reported [2,3,5,6]. However, the main challenge of this imaging method to date has been the lack of dual-frequency transducers that can transmit energy at a selected low frequency and simultaneous confocal detection of high frequency scattered echoes [1].…”
Section: Introductionmentioning
confidence: 99%
“…For CE-IVUS imaging, studies have shown that lower frequency (1-3 MHz) acoustic waves can excite microbubbles more effectively since it is close to the resonant frequency of microbubble contrast agents [10][11][12]. Microvascular images obtained with such 2 MHz transmission and 30 MHz receiving approach were demonstrated to have very high resolution and contrast to tissue ratios (CTR), producing high quality images similar to x-ray angiography, and thus dual frequency ultra-broadband contrast imaging approach is referred to as "acoustic angiography" [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This technique has recently gained renewed interest in the form of acoustic angiography 6 . The higher harmonics, even more than the second one, feature narrower -6 dB beam widths (increasing lateral resolution), a shorter time pulse (increasing axial resolution), increased reduction of side lobes, and higher contrast to tissue ratio.…”
Section: Introductionmentioning
confidence: 99%